Simple Shearing Flows in Polyisobutylene Solutions - Zapas, L. J. (J Res Natl Bur Stand A Phys Chem, 1971)
Measurements of shear stress for various shearing flow histories at 25 °C are correlated through the BKZ elastic fluid theory. The data are on 10 percent PIB solution in cetane. The histories include single step stress relaxation, suddenly applied steady shear, steady shearing flow, stress relaxation after steady shear.